Paradoks Penyidik Pegawai Negeri Sipil Dalam Sistem Peradilan Pidana Indonesia - Basuki Basuki; Muhammad Mustofa; Ramlani Lina Sinaulan (Jurnal Penelitian Hukum Legalitas, 2021)
Problems deviation between the expected role and should by Civil Servant Investigators (investigators) are overlapping in charge. It is essentially a paradox. This study uses a normative law research. To obtain accurate data, researchers used the literature study technique, which consists of primary, secondary, and tertiary legal materials. Data obtained from the results of library research will be analyzed qualitatively with descriptive methods. From the research results obtained, firstly in carrying out an investigation, PPNS must follow the applicable legal norms because it is a reflection of legal certainty as well as the obligation to coordinate with the Supervisory Coordinator as a requirement for the application of the principle of legality in all its forms (due process of law), namely that all government actions must based on legal and written laws and regulations. Second, certain Civil Servants who are given the authority by law to carry out investigations in accordance with the laws which are their respective legal bases are subordination of the executive branch not included in the Indonesian Criminal Justice System, therefore the Criminal Procedure Code strictly regulates that the PPNS relationship is under coordination. and supervision of police investigators.